Detoxifying the Child and Family Welfare System for Australian Indigenous Peoples: Self-determination, Rights and Culture as the Critical Tools - Bamblett, Muriel; Lewis, Peter (First Peoples Child & Family Review, 2007)
The toxic environment that is colonized Australia has broken many of the traditional circles of care for Indigenous children and created a service system which waits for Indigenous families to become dysfunctional before there is any response. The Victorian Aboriginal Child Care Agency (VACCA) encourages an approach to Indigenous children and families which is culturally respectful, culturally appropriate and framed according to the need to respect self-determination and human rights. VACCA has developed early childhood and family welfare policies which identify how cultural-strengthening works as a preventative measure to address risk factors for Indigenous children. With the ongoing reforms to Child and Family Welfare arising from the Children, Youth and Families Act, the Victoria State Government in Australia has an historic opportunity to lead the nation in creating an Indigenous-led child and family service system which focuses on issues of prevention and early intervention. The new Act prioritizes cultural and community connection in the best interest principles for Indigenous children, recognizes self-determination and requires generalist children’s welfare services to be culturally competent. The only way to ensure that every Indigenous child is effectively cared for is by developing the capacity of Indigenous communities to look after their own by strengthening Indigenous organizations and agencies. It is Indigenous agencies who are best placed to deliver innovative programs which are culturally embedded and carefully targeted to restore the circles of care for Indigenous kids. Aculturally competent service system is what is needed to ensure better outcomes for Indigenous children.